Menelusuri Dialog Agama dalam Sejarah - Muhamad Ubaydillah; Amin Nurdin (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
This study examines the dynamics of interreligious dialogue throughout history, both in the global sphere and within the Indonesian context. Interfaith dialogue is regarded as an essential means of fostering harmony, preventing conflict, and strengthening cross-faith understanding. The research traces the development of dialogue from the Second Vatican Council, the efforts of the Anglican Church, initiatives by international Islamic organizations, to Indonesia’s own experiences, which have been marked by interreligious tensions, particularly during the New Order era and the Maluku conflicts. The findings indicate that interreligious dialogue takes place not only at the theological level but also in everyday life, social action, ethical engagement, and even within intra-faith contexts. Supporting factors include openness, commitment, and social concern, while obstacles encompass identity politics, discrimination, and issues of religious propagation. This study affirms that interreligious dialogue is not merely an ultimate goal but an essential religious way of life for the realization of genuine harmony and social justice in multicultural societies.